Outcome assessment in dermatology clinical trials and cochrane reviews: call for a dermatology‐specific outcome taxonomy. (11th September 2020) - Lange, T.; Kottner, J.; Weberschock, T.; Hahnel, E.; Apfelbacher, C.; Brandstetter, S.; Dreher, A.; Datzmann, T.; Burden‐Teh, E.; Rogers, N.K.; Spuls, P.; Grainge, M.J.; et al.
Abstract: Background: Standardized outcome reporting is crucial for trial evidence synthesis and translation of findings into clinical decision‐making. The OMERACT 2.0 Filter and COMET outcome domain taxonomy propose frameworks for consistent reporting of outcomes. There is an absence of a uniform dermatology‐specific reporting strategy that uses precise and consistent outcome definitions. Objectives: Our aim was to map efficacy/effectiveness outcomes assessed in dermatological trials to the OMERACT 2.0 Filter as a starting point for developing an outcome taxonomy in dermatology. Methods: We critically appraised 10 Cochrane Skin Reviews randomly selected from all 69 Cochrane Skin Reviews published until 01/2015 and the 220 trials included covering a broad spectrum of dermatological conditions and interventions. Efficacy/effectiveness outcomes were mapped to core areas and domains according to the OMERACT 2.0 Filter. The extracted trial outcomes were used for critical appraisal of outcome reporting in dermatology trials and for the preliminary development of a dermatology‐specific outcome taxonomy. Results: The allocation of 1086 extracted efficacy/effectiveness outcomes to the OMERACT 2.0 Filter resulted in a hierarchically structured dermatology‐specific outcome classification. In 506 outcomes (47%), the outcome concept to be measured was insufficiently described, hindering meaningful evidence synthesis. Although the core areas assessed in different dermatology trials of the same condition overlap considerably, quantitative evidence synthesis usually failed due to imprecise outcome definitions, non‐comparable outcome measurement instruments, metrics and reporting. Conclusions: We present an efficacy/effectiveness outcome classification as a starting point for a dermatology‐specific taxonomy to provide trialists and reviewers with the opportunity to better synthesize and compare evidence. Abstract : Linked Commentary: A. Ragamin et al. J Eur Acad Dermatol Venereol 2021; 35: 276‐277. https://doi.org/10.1111/jdv.17103 .